2022
DOI: 10.3389/fpsyt.2022.1032419
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Listening Visits for emotionally distressed mothers of hospitalized newborns: Proof-of-concept

Abstract: ProblemNewborn admission to the neonatal intensive care unit (NICU) is stressful. Yet in clinical practice, at best, NICU mothers are screened for depression and if indicated, referred to a mental-health specialist. At worst, no action is taken. Listening Visits, an empirically supported nurse-delivered intervention addressing emotional distress, can be conveniently provided by a NICU nurse. Prompted by the need to minimize face-to-face contacts during the pandemic, the primary purpose of this small pilot tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…This RCT was halted because of the COVID-19 pandemic. To evaluate Listening Visits delivered by NICU nurses via zoom (Segre et al, 2022), a subsequent open-pilot trial enrolled women from February 2021 to May 2022. Procedures for both trials were approved by the University's institutional review board (IRB) and registered with a single Clinical Trials.gov.…”
Section: Methodsmentioning
confidence: 99%
“…This RCT was halted because of the COVID-19 pandemic. To evaluate Listening Visits delivered by NICU nurses via zoom (Segre et al, 2022), a subsequent open-pilot trial enrolled women from February 2021 to May 2022. Procedures for both trials were approved by the University's institutional review board (IRB) and registered with a single Clinical Trials.gov.…”
Section: Methodsmentioning
confidence: 99%
“…The infant's health continued to be a prominent focus, either concerns over deteriorating health or celebrations of improving health and parenting milestones, e.g., being able to hold the baby for (Percival et al, 2017); all key components of Listening Visits. Together, NICU mothers' positive views as well as empirical support for the effectiveness of Listening Visits ( McCabe et al, 2021) including in the NICU (Segre et al, 2013;Segre et al, 2022;Segre et al, 2023) justifies our new focus: refining and codifying Listening Visits to facilitate its integration into routine clinical care. Important decisions that need to be made include, but are not limited to, determining eligibility for Listening Visits (e.g., mothers vs. depressed mothers, mothers only vs. mothers and fathers, etc.…”
Section: Initial Sessions (1 and 2)mentioning
confidence: 99%
“…Although embedded design examines cases at more than one level, a holistic design focuses on cases' global nature and aims to understand phenomena in real-world situation, a colla borative partnership, and em powering the mother. Clinical trial evaluations of Listening Visits in the NICU setting found promising outcomes (Segre et al, 2013;Segre et al, 2022;Segre et al, 2023); and that NICU mothers value this approach (Segre et al, 2016).…”
Section: Case Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Essa intervenção foi concebida para cuidado de mulheres com sintomas de tristeza e ansiedade pós-parto (7) . Posteriormente, pesquisadoras norteamericanas adaptaram a intervenção de forma que pudesse ser implementada por enfermeiros (7,8) e promoveram junto a esses profissionais oficinas didáticas e atividade de simulação, a fim de desenvolver habilidades de empatia, colaboração, não diretividade e autonomia/apoio (9,10) . A intervenção citada ainda não foi desenvolvida nos países da América Central de do Sul, o que remonta a importância desse conhecimento aos enfermeiros que atuam nessa localidade.…”
Section: Introductionunclassified